أثر إدارة التغيير في تعزيز فعالية النظام الضريبي - شقلوفد.محمد فرج; الشتيويد.حسني رمضان; العماريد.امباركة سالم (Aljameai, 2022)
الملخص: هدفت هذه الدراسة إلى التعرف على أثر إدارة التغيير بأبعادها) التغيير في الثقافة، التغيير في الهيكل التنظيمي، التغيير في التكنولوجيا، التغيير في المهام (على فعالية النظام الضريبي بالتطبيق على مصلحة الضرائب طرابلس. ولتحقيق أهداف هذه الدراسة استخدم المنهج الوصفي، وتم جمع البيانات اللازمة عن طريق الاستبانة المعدة لذلك، وكان مجتمع الدراسة يتكون من فاحصي الضرائب في إدارات ومكاتب مصلحة الضرائب طرابلس، وقد تم أخذ عينة منهم وكانت بحجم (55) مفردة. وتوصلت الدراسة إلى مجموعة من النتائج، كان من أبرزها: أن لأبعاد إدارة التغيير والمتمثلة في (التغيير في الثقافة، التغيير في الهيكل التنظيمي، التغيير في التكنولوجيا، التغيير في المهام (أثر واضح على فعالية النظام الضريبي بمصلحة الضرائب طرابلس. Abstract: This study aimed to identify the impact of change management dimensions (change in culture, a change in the organizational structure, change in technology, and the change in the tasks) to enhance the effectiveness of the tax system by applying to tax governance in Tripoli City. In order to achieve the objectives of the study, the researchers followed the descriptive approach. The data necessary for the study were collected by means of the questionnaire prepared for this research. The study population consisted of the employees at tax governance in Tripoli City whereas a sample was taken from them. The size of (55) questionnaire was returned, and the researchers reached a set of results. the most important of which were: The dimensions of change management represented in: (change in organizational structure, change by technology, change in culture, change in the tasks) affect the effectiveness of the tax system in Tripoli tax governance.